The Effect of Age, Gender, and Insertion Site on Marginal Bone Loss around Endosseous Implants: Results from a 3-Year Trial with Premium Implant System - Negri, Massimiliano (Hindawi Publishing Corporation, 2014)
Objectives. The goal of this study was to evaluate bone changes around endosseous implants in partially edentulous patients. Materials and Methods. A total of 632 two-stage implants were placed in 252 patients. The implants had straight emergence profile, ZirTi surface, 3.3 to 5 mm diameter, and 8.5 to 13 mm length. Bone levels were assessed on orthopantomography immediately after surgery and after 36 months and marginal bone loss (MBL) was calculated from their difference. Results. Cumulative survival rate was 98.73%. Overall MBL was 0.8 mm ± 0.03 (mean ± SEM). Higher MBL was observed around implants in the maxilla than in the mandible (P < 0.007). A relation between implant diameter and MBL (P < 0.0001) was observed in male and, more limitedly, female patients. Older patients had higher MBL in the maxilla, but not in the mandible (P < 0.0001). MBL progressively increased with age in male patients, but reached a peak already in the 50–60 years age group in the female subset (P < 0.001). Conclusions. The overall MBL is consistent with the available literature. Site difference and patient age and gender appear to significantly affect MBL, representing important factors to be considered during implant placement.